Face Recognition Implementation with MTCNN on Attendance System Prototype at Trisakti University - Muhammad Azamy; Anung B. Ariwibowo; Is Mardianto (Indonesian Journal of Banking and Financial Technology, 2023)
This study aims to implement Face Recognition with MTCNN on Attendance System Prototype at Trisakti University. People work hard to be faster in all parts of life due to the rapid development of technology, which has generated numerous innovations that aid them in their day-to-day tasks. The rapid growth of technology is evident in multiple arenas, including academics. Maintaining the accuracy of attendance data collecting is crucial for all educational institutions because it determines the institution's educational excellence. The word "tipsen" or delegated attendance circulates among academics as an example of data manipulation. To mitigate this, the author attempts to develop a biometric attendance system based on face recognition.